Audiology and speech pathology as emerging medical health fields - Zeb, Dania; Zeb, Ayesha; Tariq, Zoya (Journal of the Pakistan Medical Association, 2025)
Hearing and communication skill are crucial for working and learning in order to become responsible citizens for one’s country. A spectrum of illnesses ranging from mental health issues to congenital and genetic disorders, as well as inborn errors of metabolism all tend to cause speech and hearing disabilities hindering human capability and making their life difficult1. Hearing impairment is increasingly being recognised in young population due to overuse of hearing devices. This has triggered the need for hearing and communication rehabilitation. Speech and language pathologists are equipped to diagnose these conditions and provide assisted technology in order to treat them effectively, but unfortunately in developing world countries like Pakistan awareness and knowledge among people is scarce therefore, many people find these services unaffordable, inaccessible, and unattainable 2. Therefore, I am writing this letter to raise concern regarding limited knowledge of allied medical fields of audiology and speech pathology among general population and healthcare workers. Even medical students tend to overlook these fields in favour of psychology, which, in hindsight, deals with many patients with similar conditions. The lack of awareness can be attributed to incomplete curricula devoid of digital tools and latest technologies necessary to comprehend the basics of these emerging allied health fields3. Owing to the paradigm shift in healthcare in Pakistan, there is an increased demand for audiologists and speech pathologists, particularly in children needing cochlear implants, in teenagers with the onslaught of wired and wireless headphones and in the elderly population. Another point of note is that hearing aids, cochlear implants and other rehabilitation services are costly which hinders public access. However, if more medical students choose audiology or speech pathology as a career option and raise awareness, it could pave the way for locally invented and assembled devices at competitive prices, thereby lowering costs4. Furthermore, the importance of competent audiologists and speech pathologists in early diagnosis and prompt treatment of developmental language disorders i.e. Autism SDs, cannot be negated. They are considered as early providers as they are able to pick communication deficits and help the children in social interaction skills and language development by improving their gestures often considered as pre-linguistic behaviours and teaching them verbal communication5. In conclusion, we urge medical field providers to raise awareness regarding these fields to utilize to their full potential and urge fellow readers to counsel people to focus on these career options to pursue medical careers with less competition with more chance of making an impact on the healthcare world.